Establishment and application of highly efficient regeneration, genetic transformation and genome editing system for cucurbitacins biosynthesis in Hemsleya chinensis - Juan Wang; Chao-Hui Li; Chun-Fan Xiang; Pin-Han Zhou; Le-Song Li; Xia Li; Sheng-Chao Yang; Guang-Hui Zhang; Yan Zhao (BMC Plant Biology)
Abstract Background Hemsleya Chinensis is a perennial plant in the Cucurbitaceae family containing antibacterial and anti-inflammatory compounds. The lack of genetic transformation systems makes it difficult to verify the functions of genes controlling important traits and conduct molecular breeding in H. chinensis. Results Highly efficient calli were induced on MS medium added 1.5 mg·L− 1 6-benzylaminopurine (6-BA) and 0.02 mg·L− 1 1-naphthylacetic acid (NAA) with high efficiency (> 95%). The frequency of shoot induction was increased to 90% with a plant growth regulator combination of 1.5 mg·L− 1 6-BA and 0.1 mg·L− 1 NAA. Our results also showed that 100% of shoot regeneration was achieved in a shoot regeneration medium. Additionally, more than 92% of kanamycin-resistant plants were confirmed. Furthermore, we achieved 42% genome editing efficiency by applying this transformation method to HcOSC6, a gene that catalyzes the formation of cucurbitadienol. HPLC analysis showed OE-HcOSC6 lines exhibited significantly higher cucurbitadienol levels than the genome-edited lines. Transcriptomic analysis revealed that some downstream genes related to cucurbitadienol biosynthesis, such as HcCYP87D20, HcCYP81Q58, and HcSDR34, were up-regulated in OE lines and down-regulated in mutants. Conclusions Here, we established a process for regeneration, transformation, and genome editing of H. chinensis using stem segments. This provides valuable insight into the underlying molecular mechanisms of medicinal compound production. By combining high-efficiency tissue culture, transformation, and genome editing systems, we provide a powerful platform that supports functional research on molecular mechanisms of secondary metabolism.